Comparação dos parâmetros de força e propriocepção entre indivíduos com e sem instabilidade funcional de tornozelo - Milanezi, Fernanda Cristina [UNESP] (2015)
After an ankle sprain 40% of individuals continue to report a sensation of joint instability that is related to musculoskeletal dysfunction called functional ankle instability (FAI). However, a mechanism like this musculoskeletal dysfunction occurs remains unknown. In this sense, the knowledge of musculoskeletal changes that occur in individuals with FAI may be an important factor to plot more effective preventive interventions. Thus, the aim of this study was to compare peak torque (PT) concentric inversion (INV) and eversion (EVE), conventional ratio (EVE/ INV) and passive joint repositioning in individuals with and without FAI in recreational athletes females. The sample consisted of 22 volunteers aged 18-25 years who were divided into control group and the group with FAI. The torque rating was performed on an isokinetic dynamometer with five maximal concentric contractions at speeds of 60 and 120 graus.s-1 in INV and EVE movement and passive joint repositioning to target angle of 10° and 20° of inversion. PT data, conventional ratio and average absolute error of the target angle were analyzed. Statistical analysis was performed using the Student t-test for independent samples. Found that individuals with LFS showed decreased evertor strength compared to control subjects, as well as unbalanced muscle ratio, which may increase the susceptibility of this group to ankle sprains.